Models and Practices of Curriculum Evaluation in Technical and Vocational Education and Training: A Systematic Literature Review - Erliza Yubarda; Hasan Maksum; Waskito Waskito (Universitas Negeri Padang, 2026)
Abstract - Curriculum evaluation is essential for ensuring the relevance, quality, and sustainability of Technical and Vocational Education and Training (TVET) in response to technological advancement, industrial transformation, and evolving workforce demands. However, existing studies primarily focus on individual evaluation models or specific institutional contexts, resulting in fragmented evidence. This study aims to identify curriculum evaluation models implemented in TVET, analyze their implementation practices, compare their characteristics, and synthesize current trends and future directions. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines using the Scopus database. The review process included identification, screening, eligibility assessment, quality assessment, and thematic synthesis, resulting in 12 eligible studies published between 2015 and 2025. The findings identified seven categories of curriculum evaluation models, namely Formal Evaluation, Quality Assurance Evaluation, Industry-Based Evaluation, Stakeholder-Based Evaluation, Competency-Based Evaluation, Future-Oriented Evaluation, and Assessment/Comparative Evaluation. The synthesis indicates a paradigm shift from traditional administrative evaluation toward more collaborative, evidence-based, competency-oriented, and industry-responsive approaches. Furthermore, the selection of evaluation models is influenced by national TVET policies, institutional priorities, and the level of industry collaboration, suggesting that no single evaluation model is universally applicable across different contexts. This study contributes a conceptual synthesis of curriculum evaluation models and highlights the importance of integrating multiple evaluation approaches to support continuous curriculum improvement, providing theoretical insights and practical guidance for curriculum developers, educational institutions, policymakers, and industry partners.Keywords : Technical and Vocational Education and Training (TVET), Curriculum Evaluation, Vocational Education, Systematic Literature Review, PRISMA 2020, Thematic Synthesis.